Marketing strategic planning and choosing the right strategy using AHP technique. Case study: Ghavamin Bank Mazandaran - Forough Sadeghpour; Mohammad Ghorbani Far; Ali Ramzan Khah; Masoumeh Amu Akbardokht Amiri (Dutch Journal of Finance and Management, 2017)
The main purpose of this study was to identify the right strategy marketing plan Ghavamin Bank in Mazandaran province Analytical Hierarchy Process (AHP) have been. The study of the target application, based on the nature and control variables descriptive non-experimental research is quantitative data that is collected by Operations Research. Due to the above, this study is a descriptive survey research. Study the Analytical Hierarchy Process (AHP) Was to gather information through questionnaires paired comparison Comments 15 experts to decide and prioritize factors have been taken. The results showed that by hierarchical validity and reliability of research tools for measuring components has been desired. In determining the priority of various factors, the results showed that the factors that should be prioritized in the strategic planning of marketing Ghavamin Bank considered by managers include: economic factors, competition, communication with customers and prospects, and future plans.
Keywords: 650; strategic planning; marketing; strategic planning; marketing; Ghavamin Bank Mazandaran